EVALUATION OF CORN HYBRIDS PERFORMANCE IN TWO LOCATIONS OF GOIÁS (REVISTA DE AGRICULTURA NEOTROPICAL, 2019)
The objective of this study was to evaluate the agronomic traits and grain yield of corn hybrids in two locations of the North Central region of Goiás. The experimental design was a randomized block, in the 17x2 factorial scheme (17 hybrids and two locations) with four replications. The locations were Itapaci and Ceres. Each plot consisted of two rows of five meters, spaced 0.50 m and rows were sown on the sides, which served as a border. The evaluations occurred in the two central rows, excluding 0.50 m at the extremities. The variables analyzed were: first ear height, plant height, stem, number of ears per plant, number of grain rows, number of grains per row, 1000 grain weight and grain yield (kg ha-1). The hybrids that showed the best conditions for plant height were DKB 290 PRO 3, DKB 290 PRO 2, DKB 310 PRO 2, DAS 2B810 PW, DKB 390 PRO 2 and AS 1633 PRO 2, with emphasis on DKB 310 PRO 2, which also showed satisfactory first ear height and stem and ear diameter. About grain yield, the hybrids MG 652 PW, AGN 30A37 PW, STATUS, DKB 310 PRO 2, AG 7098 PRO 2, MG 600 PW and IMPACTO presented highest grain yield performance in both municipalities.